KEMAMPUAN REPRESENTASI MATEMATIS SISWA PADA MATERI SEGITIGA - Monika Sari; Edy Yusmin; Ahmad Yani T (Jurnal AlphaEuclidEdu, 2021)
AbstractThe mathematical representation ability referred to in this study is the ability to express mathematical ideas or ideas to solve a problem with various mathematical representations of visual forms (pictures) and verbal forms (writing).This type of research is descriptive with a qualitative approach which aims to describe systematically the ability of visual mathematical representations and the ability of verbal mathematical representations.The data collection technique in this study was carried out using essay. Test questions were given to student an grade VIII A at SMP Negeri 1 Mandor, where there were three groups, namely the upper, middle, and lower group. Students who will be interviewed are selected based on the representation ability test scores where only two students will represent for each group.The results showed that the ability of visual mathematical representation when given verbal form questions to answer indicators using pictures was in the percentage of students' average score 66.67% and the ability of verbal mathematical representation if given visual questions, for the answer indicator using words is in the percentage of the student's average score of 33.33%. Students still have difficulty with verbal representation if given a visual form. Keywords: visual representation, verbal representation and trangle material